Dicarbonyls and Advanced Glycation End-Products in the Development of Diabetic Complications and Targets for Intervention - Brings, Sebastian (Int J Mol Sci, 2017)
Advanced glycation end-products (AGEs) are non-enzymatic protein and amino acid adducts as well as DNA adducts which form from dicarbonyls and glucose. AGE formation is enhanced in diabetes and is associated with the development of diabetic complications. In the current review, we discuss mechanisms that lead to enhanced AGE levels in the context of diabetes and diabetic complications. The methylglyoxal-detoxifying glyoxalase system as well as alternative pathways of AGE detoxification are summarized. Therapeutic approaches to interfere with different pathways of AGE formation are presented.